Budaya Literasi Digital-AI dalam Pendidikan Agama Islam: Penguatan Tabayyun Digital dan Integritas Akademik - Ais Isti'ana (WISE Pendidikan Indonesia, 2026)
Generative artificial intelligence (GenAI) has transformed how students access information, construct arguments, and complete academic tasks. In Islamic Religious Education (PAI), this transformation is not only technological but also epistemic and ethical because religious knowledge requires source validity, contextual interpretation, scholarly authority, and teacher guidance. This study aims to formulate an AI-digital literacy culture framework for strengthening digital tabayyun and academic integrity in PAI learning. Using an integrative literature review, this study synthesized 40 publications published between 2004 and 2026, with 37 publications concentrated in 2019–2026. Data were analyzed through literature extraction, thematic coding, and conceptual synthesis. The findings show that AI-digital literacy culture in PAI consists of six operational dimensions: information access literacy, AI limitation literacy, critical prompting literacy, digital tabayyun, academic integrity, and scholarly authority literacy. These dimensions indicate that AI can support exploratory learning, but its output must be verified through credible religious, academic, and pedagogical sources. The novelty of this study lies in transforming digital tabayyun from a moral recommendation into an observable academic procedure. The study implies that teachers, schools, and madrasahs need AI-use guidelines, source-verification rubrics, process-based assessment, and transparent AI disclosure to promote ethical and accountable learning in PAI.